Microstructure and Properties of ER50-6 Steel Fabricated by Wire Arc Additive Manufacturing. (5th August 2021) - Hu, Qingxian; Miao, Junyan; Wang, Xiaoli; Li, Chengtao; Fang, Kewei
Abstract : In this paper, ER50-6 steel was fabricated by wire arc additive manufacturing (WAAM) with an A-W GTAW system. The microstructure, mechanical properties, and corrosion behaviors of ER50-6 steel by WAAM were studied. The results showed that, with the GMAW current increased, from the bottom to the top of the sample, the microstructure was fine ferrite and granular pearlite, ferrite equiaxed grains with fine grains at grain boundaries, and columnar ferrite, respectively. The average hardness in the vertical direction of samples 1# and 2# was 146 and 153 HV, respectively. The hardness of sample 2# increased because of the refinement of grain. The pores in the sample increased as the bypass current increased. The higher bypass current also has a deterioration effect on the corrosion behavior of ER50-6 steel.